REVITALIZING CULTURE THROUGH NOCTURNAL TOURISM IN YOGYAKARTA: TRENDS, STAKEHOLDERS, AND A CONCEPTUAL FRAMEWORK - Christianto, Jery; Gunawan, Leonardo (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2025)
This study explores the evolving phenomenon of nocturnal tourism and its strategic role in revitalizing cultural and artistic expressions, with a specific focus on Yogyakarta, Indonesia. Employing a qualitative literature review and thematic analysis, this paper synthesizes scholarly findings to develop a conceptual framework of nocturnal tourism grounded in cultural preservation, technological integration, and stakeholder engagement. The results reveal that nocturnal tourism in Asia has expanded through diverse cultural practices, nature-based attractions, and tech-enhanced experiences. Yogyakarta demonstrates high potential to adopt these trends by leveraging its rich cultural heritage, night-time traditions, and digitally literate youth. Key findings underscore the importance of community-led initiatives, adaptive spatial planning, and sustainable governance to ensure inclusive and resilient night tourism ecosystems. The study proposes a circular framework built on four pillars: cultural anchoring, tech-enabled sustainability, stakeholder inclusion, and regenerative impact metrics. This conceptual model not only highlights the cultural and socio-economic contributions of nocturnal tourism but also serves as a strategic tool for cultural cities navigating post-pandemic tourism recovery and sustainable urban development.